2021
DOI: 10.1261/rna.078703.121
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high-confidence human poly(A) RNA isoform scaffolds using nanopore sequencing

Abstract: Nanopore sequencing devices read individual RNA strands directly. This facilitates identification of exon linkages and nucleotide modifications; however, using conventional methods the 5′ and 3′ ends of poly(A) RNA cannot be identified unambiguously. This is due in part to the architecture of the nanopore/enzyme-motor complex, and in part to RNA degradation in vivo and in vitro that can obscure transcription start and end sites. In this study, we aimed to identify individual full-length human RNA isoform scaff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…To verify these results, we reanalyzed human GM12878 poly(A) RNA data using Guppy v. 6.3.2 (default quality score cutoff = 7). For our group's data in the Workman study (~2.6 million reads) 6 and for the Mulroney et al study (~3.8 million reads) 10 , we found median accuracies of 90.6% and 89.8%, respectively, in agreement with the published results.…”
Section: State-of-the-art Nanopore Drssupporting
confidence: 89%
See 2 more Smart Citations
“…To verify these results, we reanalyzed human GM12878 poly(A) RNA data using Guppy v. 6.3.2 (default quality score cutoff = 7). For our group's data in the Workman study (~2.6 million reads) 6 and for the Mulroney et al study (~3.8 million reads) 10 , we found median accuracies of 90.6% and 89.8%, respectively, in agreement with the published results.…”
Section: State-of-the-art Nanopore Drssupporting
confidence: 89%
“…This obscures the true identity of that strand end. In our hands, even when we demonstrably sequenced poly(A) RNA from the 3′-poly(A) tail to the 5′-m7G cap, we could not resolve the final six nucleotides 10 . Consequently, it is important that investigators either achieve truly full-length reads or that they define what is meant by the term.…”
Section: Further Technical Improvements To Broaden Nanopore Drs Usementioning
confidence: 80%
See 1 more Smart Citation
“…Although several works have shown that this technology can also be used to study short RNA molecules, such as snoRNAs and snR-NAs 96,98 , DRS is inefficient at capturing RNA molecules shorter than 200 nucleotides (nt) and is generally considered unable to capture sequences shorter than ~100 nt 96,97 , limiting its applicability to study short RNA populations, such as tRNAs. In addition, the first ~15 nt at the 5′ end of RNA molecules are typically lost in DRS runs 93,99 , as this portion cannot be adequately basecalled due to the increase in the RNA translocation speed when the 5′ end of the molecule exits the helicase 99 . To overcome these limitations, we reasoned that extension of the 5′ and 3′ ends of the tRNA would lead to improved sequencing of tRNA molecules, as these would now be beyond the ~100-nt threshold, in addition to capturing the sequence and modification information of 5′ tRNA ends.…”
Section: Standard Nanopore Drs Results In Low Trna Sequencing Yieldsmentioning
confidence: 99%
“…However, the classification of reads as full-length in Bambu is influenced by both sequencing and alignment errors as well as RNA degradation, with non-unique full-length reads still being ambiguous. Approaches have been developed to enrich full-length reads experimentally 38 , or selectively analyse full-length reads during quantification 39 . These approaches are more effective in identifying which transcripts are truly expressed, however, as they significantly reduce the number of reads used for quantification, the overall abundance estimates are likely to be less accurate.…”
Section: Discussionmentioning
confidence: 99%